2019
DOI: 10.1038/s41593-018-0330-y
|View full text |Cite
|
Sign up to set email alerts
|

Dorsolateral septum somatostatin interneurons gate mobility to calibrate context-specific behavioral fear responses

Abstract: Adaptive fear responses to external threats rely upon efficient relay of computations underlying contextual encoding to subcortical circuits. Brain-wide analysis of highly co-activated ensembles following contextual fear discrimination identified the Dorsolateral septum (DLS) as a relay of the dentate gyrus-CA3 circuit. Retrograde mono-synaptic tracing and electrophysiological whole-cell recordings demonstrated that DLS somatostatin-expressing interneurons (SST-INs) receive direct CA3 inputs. Longitudinal in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(107 citation statements)
references
References 60 publications
5
102
0
Order By: Relevance
“…Fos expression was specific to vBNST, insofar as backward and forward rats did not differ in 396 overall levels of Fos in dBNST or ovBNST. Similarly, others have shown elevated Fos expression, 397 in regions in or near vBNST after stress or conditioned fear-related behavior [(Besnard et al, 2019;398 Sterrenburg et al, 2012;Verma et al, 2018); also, see Radley and 399 Sawchenko, 2011)]. 400…”
Section: Backward Css Selectively Increase Fos Expression In Mpfc Affmentioning
confidence: 88%
“…Fos expression was specific to vBNST, insofar as backward and forward rats did not differ in 396 overall levels of Fos in dBNST or ovBNST. Similarly, others have shown elevated Fos expression, 397 in regions in or near vBNST after stress or conditioned fear-related behavior [(Besnard et al, 2019;398 Sterrenburg et al, 2012;Verma et al, 2018); also, see Radley and 399 Sawchenko, 2011)]. 400…”
Section: Backward Css Selectively Increase Fos Expression In Mpfc Affmentioning
confidence: 88%
“…One mechanism is that information pertaining to certain and ambiguous threats computed in dHC and vHC is relayed to the amygdala, prefrontal cortex, and hypothalamus by vHC outputs. Alternatively, computations underlying certain and ambiguous threats are relayed directly out of the dHC and vHC through distinct pathways and integrated at extrahippocampal sites, such as the DLS (Besnard et al, 2019;Fanselow and Dong, 2010;Luo et al, 2011;Risold and Swanson, 1996) or thalamus (Fanselow and Dong, 2010;Liberzon and Abelson, 2016;Vertes, 2006;Xu and S€ udhof, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The DLS, a brain region comprised of a heterogeneous population of inhibitory neurons, by virtue of receiving direct hippocampal synaptic inputs, is ideally positioned to relay DG-CA3 computations resolving overlapping contextual information to the hypothalamus and the supramammilary nucleus (SUM) (McGlinchey and Aston-Jones, 2018; Pan and McNaughton, 2004;Risold and Swanson, 1996, 1997a, 1997bSheehan et al, 2004;Yang, 2015, 2016), a potent modulator of defensive behavior (Blanchard et al, 1998) (exploration, freezing), arousal, and stress responses (Campeau and Watson, 2000;Pan and McNaughton, 2004). We recently found that within the DLS, somatostatin (SST)-expressing neurons receive monosynaptic inputs from hippocampal CA3, CA1, and subiculum and these neurons gate mobility in aversive contexts (Besnard et al, 2019). Together, these observations suggest that contextual information may be relayed out of CA3 by CA1 or the DLS to cortical and subcortical circuits to calibrate fear responses.…”
Section: Introductionmentioning
confidence: 99%
“…To initialize our algorithm we use the CNMF-E algorithm on a short initial batch of data of length T b , (e.g., T b = 200). The sufficient statistics are initialized from the components that the offline algorithm finds according to Eqs (11,12).…”
Section: /24mentioning
confidence: 99%
“…This prevalent algorithm (see [6] for an alternative proposal) has been widely used to study neural circuits in cortical and subcortical brain areas, e.g. prefrontal cortex (PFC) and hippocampus [5], as well as previously inaccessible deep brain areas, such as striatum [7], amygdala [8], substantia nigra pars compacta (SNc) [9], nucleus accumbens [10], dorsolateral septum [11], parabrachial nucleus [12], and other brain regions.…”
Section: Introductionmentioning
confidence: 99%